Pharmacological, toxicological and phytochemical analysis of Spondias dulcis parkinson - Fernandes, Felipe Hugo Alencar [UNESP]; Soares, Sabrina da Silva; Bekbolatova, Elmira; Boylan, Fábio; Salgado, Hérida Regina Nunes [UNESP] (Taylor & Francis, 2023)
Spondias dulcis Parkinson have been used in traditional medicine in Asia, Oceania, and South America, for different diseases conditions and as a functional food. The scientific literature described as different potential pharmacology such as antioxidant, anti-inflammatory, antimicrobial, thrombolytic and enzymatic inhibitor. This study aimed to: (1) establish the pharmacological activity in intestinal motility in vivo and antioxidant activity in vitro; (2) perform the acute toxicology test in mouse; (3) characterize the phytochemical profile based on counter-current chromatography (CCC) and NMR analysis. The results revealed a laxative effect of S. dulcis extract and a high antioxidant activity (IC50 = 5.10 for DPPH assay and 14.14 for hydrogen peroxide scavenging test). No side effects were observed in the oral acute toxicity test for a dose up to 2000 mg/kg. The chemical profile was identified by CCC and NMR, and the comparison of the data obtained with previous literature revealed the presence of the flavonoid rutin (Quercetin-3-O-rutinoside) in the extract.
Keywords: antioxidant activity; countercurrent chromatography; Laxative activity; rutin